PENERAPAN METODE HIRARC UNTUK ANALISIS RISIKO KESELAMATAN KERJA PADA CONTAINER CRANE DI PELABUHAN PETI KEMAS BITUNG - Rumondor, Inzaghi; Arungpadang, Tritiya A R; Mende, Jefferson (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2024)
The causes of work accidents can come anytime, anywhere and to anyone. The risk can be fatal or just a minor accident, depending on the level of opportunity. To minimize the number of work accidents, it is necessary to take anticipatory steps from both the workers and the company management. This research focuses on reducing the impact of work accidents by analyzing the risks of hazards that can occur in every job. Researchers research using the HIRARC method for efforts to prevent and reduce the potential for work accidents, avoid and minimize risks that occur appropriately by avoiding and minimizing the risk of work accidents and controlling fiber in order to carry out the activity process so that the process becomes safe. Based on the results of hazard identification, there are 9 sources of danger on the container crane at Container Port of Bitung with 1 hazard risk has a high risk level (H) / High, 6 hazard risks have a high risk Moderate (M) / Medium, and 2 hazard risk has a high risk level Low (L) / Low. Keywords : K3, Loading and Unloading Process, HIRARC.